Faktor-Faktor Penyebab Penggunaan Variasi Idiolek dalam Tuturan Nadia Omara: Penelitian - Syafira Fitri Dahlan; Sayama Malabar; Herman Didipu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to describe the characteristics of idiolect variation, the factors influencing idiolects, and the relevance of Nadia Omara's idiolect in the special Nusantara horror story videos on the YouTube channel to the teaching of the Indonesian language in junior high schools. This study uses a qualitative descriptive method. Data collection is conducted through the observation method, recording technique, and note-taking technique. The data is analyzed by marking, classifying, determining, analyzing, describing, and concluding. The results of the study show that (1) there are three characteristics of idiolect variation including voice color, word choice, and language style. (2) The factors that influence idiolect variation are environmental factors and factors related to the background of the area of origin. (3) Idiolects have relevance to the teaching of the Indonesian language in junior high school concerning narrative text materials.